Development and Applications of Chromosome-Specific Cytogenetic BAC-FISH Probes in S. spontaneum - Dong, Guangrui; Shen, Jiao; Zhang, Qing; Wang, Jianping; Yu, Qingyi; Ming, Ray; Wang, Kai; Zhang, Jisen (Frontiers in Plant Science, 2018)
Saccharum spontaneum is a major Saccharum species that contributed to the origin of modern sugarcane cultivars, and due to a high degree of polyploidy is considered to be a plant species with one of the most complex genetics. Fluorescence in situ hybridization (FISH) is a powerful and widely used tool in genome studies. Here, we demonstrated that FISH based on bacterial artificial chromosome (BAC) clones can be used as a specific cytological marker to identify S. spontaneum individual chromosomes and study the relationship between S. spontaneum and other related species. We screened low-copy BACs as probes from the sequences of a high coverage of S. spontaneum BAC library based on BLAST search of the sorghum genome. In total, we isolated 49 positive BAC clones, and identified 27 BAC clones that can give specific signals on the S. spontaneum chromosomes. Of the 27 BAC probes, 18 were confirmed to be able to discriminate the eight basic chromosomes of S. spontaneum. Moreover, BAC-24, BAC-66, BAC-78, BAC-69, BAC-71, BAC-73, and BAC-77 probes were used to construct physical maps of chromosome 1 and chromosome 2 of S. spontaneum, which indicated synteny in Sb01 between S. spontaneum and sorghum. Furthermore, we found that BAC-14 and BAC-19 probes, corresponding to the sorghum chromosomes 2 and 8, respectively, localized to different arms of the same S. spontaneum chromosome, suggesting that there was an inter-chromosomal rearrangement event between S. spontaneum and sorghum. Our study provides the first set of chromosome-specific cytogenetic markers in Saccharum and is critical for future advances in cytogenetics and genome sequencing studies in Saccharum.